(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Needle stick injuries (NSIs) remain a major occupational hazard for healthcare workers (HCWs), leading to potential exposure to blood-borne pathogens such as HBV, HCV, and HIV. Despite global awareness, under-reporting persists in many healthcare settings in Pakistan. Objective: To determine the incidence and reporting patterns of NSIs among healthcare workers at Nishtar Hospital, Multan, during a 1-year surveillance period and to identify associated risk factors and preventive gaps. Methods: A descriptive, prospective surveillance study was conducted from January to December 2024 at Nishtar Hospital. Data were collected through direct observation, incident reports, and infection-control logs using WHO-validated forms. A total of 350 HCWsincluding nurses, doctors, technicians, and students were monitored. Variables included frequency, department, device type, reporting behavior, and post-exposure management. Data were analyzed using SPSS version 26; descriptive and inferential statistics (Chi-square, p < 0.05) were applied. Results: A total of 47 NSIs were formally reported, corresponding to an incidence rate of 3.2 per 100 HCWs per year. However, survey data indicated that approximately 58% of incidents went unreported, suggesting a true incidence of around 350 NSIs annually. Nurses (48.3%) and junior doctors (34.7%) were the most frequently affected groups, particularly those with less than two years of experience (59.2%). The Emergency and Accident Center (30.6%) and medical wards (21.8%) were the highest-risk areas. The most common causes of injury were suturing (27.9%), recapping needles (25.2%), and blood collection (22.4%), with hollow-bore needles (57.8%) as the predominant device involved. Only 62.6% of reported injuries were submitted within 24 hours. Key reasons for under-reporting included perceived low risk (55.2%), time constraints (31.9%), and lack of awareness of reporting procedures (28.4%). Statistically significant associations were found between under-reporting and limited work experience (p = 0.004), profession (p = 0.042), and incomplete HBV vaccination (p = 0.002). While 89.1% performed appropriate first aid, only 66.7% were fully vaccinated against HBV, and PEP was initiated in less than 20% of eligible cases. Conclusion: The study revealed a moderate incidence of NSIs with significant under-reporting. Nurses were the most vulnerable group, and recapping needles was the leading cause. Continuous training, strict reporting mechanisms, and universal HBV vaccination are critical to minimize occupational risk and improve safety culture at Nishtar Hospital.